2017
DOI: 10.21474/ijar01/4960
|View full text |Cite
|
Sign up to set email alerts
|

Resource Based View as a Strengthening of Industry’s Capabilities to Improve Competitive Strategies.

Abstract: Competitive advantage as the impact of the implementation company operation strategy in creating value creation on the products and services produced. Cost leadership and differentiation for products or services into a strategic part in achieving competitive advantage. Competitive strategy becomes part of the corporate strategy led to increased productivity and performance. Resource-Based View is a part of the company's capability in encouraging superior competing. This study empirically investigates whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Based on results of discussion quantitatively it can be concluded that increase of human capital, infrastructure, supply chain, science and technology have positive eff ect on competitive strategy and have positive impact on competitiveness. Human capital has signifi cant eff ect on competitive strategy (Sarjana et al, 2017b). Th e implementation of supply chain management has positive and significant impact on competitive advantage (Rahmasari 2011).…”
Section: Conclussion and Recommendationmentioning
confidence: 99%
“…Based on results of discussion quantitatively it can be concluded that increase of human capital, infrastructure, supply chain, science and technology have positive eff ect on competitive strategy and have positive impact on competitiveness. Human capital has signifi cant eff ect on competitive strategy (Sarjana et al, 2017b). Th e implementation of supply chain management has positive and significant impact on competitive advantage (Rahmasari 2011).…”
Section: Conclussion and Recommendationmentioning
confidence: 99%